The mediation role of corporate sustainability performance in the influence of corporate governance on firm performance - Zakaria, Erlanda; Damayanti, Cacik Rut; Imamah, Nur (The International Journal of Accounting and Business Society, 2025)
Purpose — This research aims to determine the mediating role of corporate sustainability performance (CSP) on the influence of corporate governance (CG) on corporate performance (FP). Design/methodology/approach — The sample data were selected according to the following criteria: the company was a non-financial company that continued to report sustainability reports using the 2016 GRI Standard from 2017 to 2022. The data was analyzed using the Partial Least Squares (PLS) method. Findings — This study shows that only CG has a significant positive effect on FP. The influence of CG on CSP, the influence of CSP on FP, and CSP's mediating role were not significant. These results differ significantly from previous studies, but it is suspected that the COVID-19 pandemic causes data anomalies. Practical implications — According to the result, CG implementation will boost FP. Therefore, the company should consider expanding its CG practice to boost its FP. In addition, increasing CSP through boosting the sustainability report does not negatively affect FP. Therefore, companies are recommended to enhance their sustainability reporting practices to improve stakeholder engagement. Originality/value — This study examines a governance system that uses a two-tier board, as practiced in Indonesia. It is expected that his case will help substantiate the implementation of CG in two-tier board governance systems in countries where this may affect their companies' financial performance. Paper type — Explanatory study